Analisis Fase Dan Waktu Siklus Simpang Apill Dalam Upaya Peningkatan Keselamatan Lalu Lintas Menggunakan Simulasi PTV Vissim dan Software Surrogate Safety Assessment Model - Arfian, Syarillah Ashar; Tuhu Prasetyo, Teguh; Wahyu Nariendra, Pradhana (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2024)
The Singkil Adiwerna intersection in Tegal Regency with a 2-phase arrangement has the potential to cause accident risks due to traffic conflicts. For this reason, it is necessary to make efforts to arrange phases to reduce traffic conflicts aimed at improving traffic safety by considering intersection performance. The analysis method uses PKJI (2023) method for intersection performance, PTV VISSIM for simulation modeling, and Surrogate Safety Assement Model Software for the number of conflicts. The results of the analysis of 2-phase conditions with a cycle time of 86 seconds have a degree of saturation of 0.60, a queue of 7.09 meters, a delay of 16.72 seconds, an intersection level of service B and a safety level with a conflict value of 452. The application of 3 phases with a cycle time of 100 seconds has a degree of saturation of 1.01, a queue of 14.02 meters, a delay of 32.74 seconds, an intersection level of service C, and a conflict value of 243 with a 46% decrease in conflict value from 2-phase conditions. If the application of 4 phases with a cycle time of 130 seconds has a degree of saturation of 1.27, a queue of 20 meters, a delay of 47.73 seconds, an intersection level of service D, and a conflict value of 104 with a 77% decrease in conflict value from the 2-phase condition. Based on PM 96 of the Ministry of Transportation, judging from the function of the road, namely a secondary collector road with a level of service of at least C, the selection of phase settings and cycle time of the APILL intersection recommends 3 phases with a cycle time of 100 seconds.